Beyond the Role: A Body-Based Approach to Acting, Imagination, and Inner Motives in Actor Training: Melampaui Peran: Pendekatan Keaktoran Berbasis Tubuh, Imajinasi, dan Motif Batin dalam Pelatihan Aktor - Dharma, Budi; Sutardi, Edi (Universitas Negeri Surabaya, 2025)
this study examines the Melbeyond the Role (